The Effect of Profitability, Corporate Social Responsibility Disclosure, Deferred Tax Expense on Tax Avoidance - Zega, Yosua; Ramadhan, Yanuar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to explore tax avoidance in Indonesia through manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Tax avoidance is a strategy used by companies to minimize their tax obligations. Tax avoidance can be examined from several factors, namely profitability, corporate social responsibility disclosure, and deferred tax liabilities. Tax avoidance is a legal action but is considered unethical because it involves efforts to minimize the amount of tax owed. This study uses a purposive sampling method with secondary data sources, namely annual reports and sustainability reports. Data processing uses SPSS with classical assumption tests and regression tests using multiple linear regression. The results show that profitability has a negative effect on tax avoidance, corporate social responsibility disclosure has no effect on tax avoidance, and deferred tax liabilities have a positive effect on tax avoidance. Meanwhile, profitability, corporate social responsibility disclosure, and deferred tax liabilities simultaneously affect tax avoidance.